Observation of a 𝐽/𝜓⁢Λ resonance consistent with a strange pentaquark candidate in 𝐵−→𝐽/𝜓⁢Λ⁢p[bar] decays - Aaij, Roel; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Kopecná, Renata; Leverington, Blake; et al. (Physical review letters, 2023)
An amplitude analysis of 𝐵−→𝐽/𝜓⁢Λ⁢‾𝑝 decays is performed using 4400 signal candidates selected on a data sample of 𝑝⁢𝑝 collisions recorded at center-of-mass energies of 7, 8, and 13 TeV with the LHCb detector, corresponding to an integrated luminosity of 9  fb−1. A narrow resonance in the 𝐽/𝜓⁢Λ system, consistent with a pentaquark candidate with strangeness, is observed with high significance. The mass and the width of this new state are measured to be 4338.2±0.7±0.4  MeV and 7.0±1.2±1.3  MeV, where the first uncertainty is statistical and the second systematic. The spin is determined to be 1/2 and negative parity is preferred. Because of the small 𝑄-value of the reaction, the most precise single measurement of the 𝐵− mass to date, 5279.44±0.05±0.07  MeV, is obtained.